Data integration framework of pharmacology databases using ontology - Phimphan Thipphayasaeng (2018)
This paper presents linked data of pharmacology domain generated with ontology as central schema. To link data from several formats, data are transformed into database format, and they are mapped to ontology. The ontology is developed with concepts provided in the dataset. Mainly, the developed ontol-ogy contains a concept of drug, disease, genetic and drug-gene interaction with their details. The ontology is used as central schema to link concepts together; thus, linked data are created. Within the linked data, we found three types of links, i.e. addition of instances, addition of attributes and changing of variable data field to a link to another table. In this paper, actual scenarios of the found links with exemplified data are explained.